HRM practices and innovative work behavior within the hotel industry in Pakistan: Harmonious passion as a mediator - Jan G; Zainal SRM; Lee MCC (Taylor and Francis Group LLC, 2021)
Innovative work behavior (IWB) forms an essential basis for obtaining competitive advantage and long-term success for organizations. Empirical research on this behavior has received limited attention in hospitality context. This study tests a conceptual model that examines how IWB can be transpired through the different aspects of HRM practices (i.e., service training, servicing empowerment, participation in decision making) via harmonious passion. Two hundred and twenty full-time employees who worked in the four- and five-star hotels in Pakistan participated in the study. The findings reported significant mediating effect of harmonious passion between the three aspects of HRM practices and IWB.
Jan, G., Zainal, S.R.M., Lee, M.C.C “HRM practices and innovative work behavior within the hotel industry in Pakistan: Harmonious passion as a mediator”. First published in Journal of “Human Resources in Hospitality and Tourism” August 2021. https://doi.org/10.10/15332845.2021.1959803
Keywords: 1503 Business and Management; 1504 Commercial Services; 1506 Tourism